Exploding the Possibilities Australian Dance Theatre's Held - Travers, Sophie (Dance Books Ltd., Alton,Hampshire (UK), 2004)
Australian Dance Theatre's Held. PALABRAS CLAVE: Australian Dance Theatre, Held, 2004 Adelaide Festival, Garry Stewart, Lois Greenfield, dance photographer, breakdance, martial arts.